2017
DOI: 10.1167/iovs.17-21846
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography of the Superficial Microvasculature in the Macular and Peripapillary Areas in Glaucomatous and Healthy Eyes

Abstract: Medically managed glaucomatous eyes show sparser superficial microvasculature in the macular area than do healthy eyes. The measurement of the macular superficial vessel density had similar diagnostic accuracy to peripapillary RNFL and macular GCC thickness for differentiating between glaucomatous and healthy eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
128
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(160 citation statements)
references
References 35 publications
27
128
0
5
Order By: Relevance
“…The area under the curve (AUC) for the best discriminating OCTA parameter (vessel density and blood flow index) ranged between 0.75 and 1.00, while for the OCT parameter (RNFL) the values ranged between 0.76 and 0.97 [17, 19, 20, 22, 23, 25, 27, 31, 32, 34, 36, 37, 41, 49]. Most studies found an AUC above 0.850 both for the OCTA parameters [17, 20, 22, 23, 25, 31, 32, 37, 41] and for the RNFL [19, 20, 22, 25, 31, 34, 37, 49].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The area under the curve (AUC) for the best discriminating OCTA parameter (vessel density and blood flow index) ranged between 0.75 and 1.00, while for the OCT parameter (RNFL) the values ranged between 0.76 and 0.97 [17, 19, 20, 22, 23, 25, 27, 31, 32, 34, 36, 37, 41, 49]. Most studies found an AUC above 0.850 both for the OCTA parameters [17, 20, 22, 23, 25, 31, 32, 37, 41] and for the RNFL [19, 20, 22, 25, 31, 34, 37, 49].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies found an AUC above 0.850 both for the OCTA parameters [17, 20, 22, 23, 25, 31, 32, 37, 41] and for the RNFL [19, 20, 22, 25, 31, 34, 37, 49]. Only 2 studies found a significant difference, with a better AUC for the RNFL [19, 34] in both cases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Auch wenn der diagnostische Stellenwert dieser neuen Untersuchungstechnik nicht abschließend eingeordnet werden kann und eine isolierte Bewertung der OCTA nicht die diagnostische Aussagekraft der eingeführten morphometrischen Methoden wie der Vermessung mittels Heidelberg Retina Tomograph (HRT) und OCT erreicht, so zeigen die neuesten Studienergebnisse im Vergleich zur zirkumpapillären Nervenfaserschicht und Gesichtsfeldparametern vergleichbare diagnostische Wertigkeiten mit AUC-Werten von 0,94 [3]. Allerdings ist der klinische Wert der OCTA besonders im Frühstadium des Glaukoms unverändert unsicher [4].…”
Section: Transfer In Die Praxis Von Prof Dr Klaus Rohrschneider (Heunclassified